DISPENSER OTOMATIS MENGGUNAKAN SENSOR ULTRASONIK BERBASIS ARDUINO UNO - Marwan Hakim (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2023)
Current technological developments are so rapid and there are many human activities, encouraging people to think they can work effectively and efficiently. One way to make work easier is to make a mechanical device automatic. The use of a dispenser for filling water into a glass can be done automatically as a substitute for a dispenser for manually filling water. With the prototype method we can design or create an Automatic Dispenser tool using ultrasonic sensors and Arduino Uno. This tool uses an Arduino Uno microcontroller as its main controller, ultrasonic sensors as input and as a measuring device when the water is full or with a specified limit, a relay as an introduction to power to the water pump which will drain water from the gallon to the measuring cup provided. From the results of the design, it makes it easy for the user because it has been automated in terms of filling and then a predetermined amount of water.